Practice and Prospects for Using the Emulator Family of IBM Mainframe Architecture - Shmid, Alexander Viktorovich (Trudy Instituta sistemnogo programmirovaniâ, 2020)
This article describes the family of emulators for IBM mainframe architectures, their development history, functional features and capability, as well as the experience of many years (since 1994) of emulators development and their implementation area. There was sold the relatively simple task (for modern standards) of creating a virtual machine in the VSE/ESA operating system for transferring legacy platform-dependent applications to this target environment. The problem was solved at first for EU computers in Russia, and then for IBM 9221 in Germany and in the other western countries. The transfer was made to the OS/390 environment, and to IBM AIX, quite modern at that time. The virtual execution of any existing IBM mainframe operating systems in the main server OS environments: Linux, Windows, AIX, Z/OS, ZLinux had been provided. There was developed the solution for combining any types of formed virtual computing nodes into heterogeneous geographically distributed computing networks that provide, in particular, multiple mutual redundancy of nodes in the network.